2015
DOI: 10.5455/ijmsph.2015.25012015109
|View full text |Cite
|
Sign up to set email alerts
|

Self-monitoring of blood glucose among diabetic patients attending Al-Eskan Primary Health Care Center in Makkah Al-Mukarramah city

Abstract: Materials and Methods: A cross-sectional analytic study was conducted including a representative sample of diabetic Patients attending Al-Eskan Primary Health Care Center in Makkah Al-Mukarramah city. Every third patient who attended for follow-up in the center was recruited in the research until the target number was achieved. Two sets of questionnaires were developed in English language and validated in a Malaysian study, and consequently used in the present study. One set of questionnaire was for diabetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…This finding agrees with a study report from Egypt where 78.6% of the study participants did not adhere to self-blood glucose monitoring ( 53 ). However, this finding does not agree with findings from Saudi Arabia (29.2%) ( 56 ), Poland (40%) ( 57 ) and Oman (64.7%) ( 58 ). Despite the increasing level of diabetic cases, advancement in technology and medicine, glycemic level controlling has been insignificant in most diabetic patients in developing countries such as Ethiopia due to glucometer unaffordability and knowledge gaps.…”
Section: Discussioncontrasting
confidence: 81%
“…This finding agrees with a study report from Egypt where 78.6% of the study participants did not adhere to self-blood glucose monitoring ( 53 ). However, this finding does not agree with findings from Saudi Arabia (29.2%) ( 56 ), Poland (40%) ( 57 ) and Oman (64.7%) ( 58 ). Despite the increasing level of diabetic cases, advancement in technology and medicine, glycemic level controlling has been insignificant in most diabetic patients in developing countries such as Ethiopia due to glucometer unaffordability and knowledge gaps.…”
Section: Discussioncontrasting
confidence: 81%
“…[ 699 ] SMBG complements HbA1c testing as it can differentiate the fasting, pre-prandial, and post-prandial hyperglycaemic levels, detect the glycaemic excursions, recognize and contribute in monitoring resolution of hypoglycaemia, and provide immediate feedback to patients about the effects of food choices, activity, and medication on glycaemic control. [ 700 ]…”
Section: B Ackgroundmentioning
confidence: 99%
“…Other variables like uncontrolled diabetes or longer duration of diabetes also did not influence sharing frequency. A similar regional study from Western Saudi Arabia demonstrated a prevalence rate of 70 % for measuring SMBG, with only 22% sharing the results with their physicians [ 23 ]. Our results showed higher rates of compliance when compared to the other regional literature.…”
Section: Discussionmentioning
confidence: 99%